Glyceraldehyde 3-phosphate dehydrogenase protein and mRNA are both differentially expressed in adult chickens but not chick embryos. - Milner, R J (1983)
We have determined the 679 nucleotide sequence of a cDNA clone which, by hybridization-translation experiments, corresponds to a 36K chick brain protein. Our studies provide a partial amino acid sequence for this protein, identifying it as chicken glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Antisera raised against purified chicken GAPDH reacted with a 36K protein present in chick brain extracts and estimated to be the fourth most prevalent protein, as determined by either Coomassie Blue staining or by in vitro translation of chick brain mRNA. The amounts of GAPDH mRNA in chick brain, liver and muscle and adult chicken brain are similar, whereas the relative amount of adult chicken muscle GPDH mRNA is greatly elevated and that of adult liver lowered. The GAPDH protein levels showed a similar variation between tissues, suggesting that the levels of GAPDH protein are largely regulated by the amount of available GAPDH mRNA. The chicken GAPDH clone does not hybridize to rat mRNA, even though GAPDH is one of the most evolutionarily conserved proteins, indicating that selection pressures are heavier at the primary protein sequence level than at the nucleic acid sequence level for this gene, a situation contrasting to that of the tubulins.